Virtual Tools and Protocols to Support Collaborative Reflection During Lesson Study - Groth, Randall; Bergner, Jennifer A.; Weaver, Starlin D.; Follmer, D. Jake (Innovations in Science Teacher Education, 2021)
Lesson study provides opportunities for teachers to collaboratively design, implement, and analyze instruction. Research illustrates its efficacy as a site for teacher learning. The setting for this article is a lesson study project involving preservice teachers, inservice teachers, and university faculty members. We supported collaborative reflection on practice among these individuals by using asynchronous and synchronous online tools and meeting protocols. Asynchronous online lesson-video review and tagging helped participants prepare to debrief about lessons they had implemented. Midway through one of our lesson study cycles, the COVID-19 pandemic occurred, eliminating opportunities to meet face-to-face for lesson debriefing sessions. In response, we developed and field-tested two protocols for online synchronous lesson study debriefing meetings. The protocols prompted conversations related to pedagogy, content, and content-specific pedagogy. After the debriefing sessions, lesson study group members reported improvements in their knowledge growth, self-efficacy, and expectations for student learning. We describe our use of online virtual tools and protocols to contribute to the literature on ways to support collaborative reflection on practice.